Analisis Potensi Komoditas Manggis di Kabupaten Purwakarta - Bumi, Agustina Rosari Ilalang; Budiraharjo, Kustopo; Handayani, Migie (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Potential analysis means searching for or exploring the potential that exists in a research object. This study aims to analyze the base location/potential location for mangosteen production, forecast the planted area, production, and productivity of mangosteen fruit, and analyze the influence of planted area, farmer exchange rate (NTP), and mature plants on mangosteen fruit production in Purwakarta Regency, West Java. This research was conducted in Purwakarta Regency, West Java. The method used is secondary data analysis. The data used in this study is secondary data. The secondary data used is time series data for 10 years from 2014 to 2023. The analytical methods used are analysis of base location using the location quotient, forecasting analysis using the least squares method, and analysis of the influence of factors using multiple linear regression analysis. This study concludes that from 2024 to 2028, The sub-districts in Purwakarta Regency that are included in the base location for mangosteen plants include Kiarapedes District, Wanayasa District, and Darangdan District. The planted area, production and productivity is predicted to increase constantly. Planted area, farmer exchange rate (NTP), and mature plants simultaneously have a significant influence on mangosteen fruit production. Farmer exchange rate (NTP) and mature plants partially have a significant influence on mangosteen fruit production while planted area did not have a significant influence on mangosteen production in Purwakarta Regency.